Amor e criatividade: ações estéticas e diversidade na construção do futuro - Leão, Heloisa Helena da Fonseca Carneiro (2009)
This work reflects the present concerns of the humankind, their inventions and their habitat. The destruction of the nature and the future of our planet are in deep jeopardy, however the new technologic discoveries has the possibility to approach man to the nature, of course, if applied rationally, at the same time sensible. The actions of the modern man are consequences of the traditional science, which places the reason as the sole and only way to the truth. Today, we noticed that the absolute truth does not exist. In consequence, by the absence of the truth, the human been, feels abandoned. As long as we try to understand questions such as diversity, the mutation and new technologies, the world becomes more complex to us. To resolve this paradox, the man needs to look deeply around the world and try to find new solutions. The confrontation between man and object on a consistent way is fundamental to build a diverse future. The search for a different world is founded in Ilya Prigogine, Charles Sanders Peirce and Edgar Morin sources of in exhaustive reflection. Prigogine affirms future is not something established in advance, yet in constant construction, he emphasizes that future is possible, if we act properly to change. In his letter, "the future generations", he convoked youngsters to act for a different tomorrow. The art is present in all human being manifestations, it is crucial to redeem the sensibility that has been lost in the tyranny of the reason. Since the beginning of humanity, man and art always been partners, this cannot be forgotten or ignored. We presented 3 artists that amplified the artistic savoir-faire. Lygia Clark proposed to the contemporary man the re-discovery of the body by the sensorial memory, Frans Krajcberg, directed his life to alert against nature destruction, Joseph Beuys invests in the individuals actions, as he considers that all individuals are artists. Thinkers, artists have shown the possibilities of the "re-enchantment of the world" utilizing the creativity and love as "future constructors". Not only them, but also people with refined sensibility are dedicating themselves to modify the future, using esthetics actions